Análisis factorial confirmatorio y propiedades psicométricas de la Escala de Desesperanza de Beck en estudiantes en contextos de pobreza en México - Quiñonez Tapia, Francisco; Méndez Luevano, Tanya Elizabeth; Castañeda-Camey, Nicté (Revista de Psicopatología y Psicología Clínica, 2019)
Abstract: Confirmatory factor analysis and psychometric properties of the Beck Hopelessness Scale in students in contexts of poverty in Mexico. Hopelessness predicts depression and suicide. In the world, suicide is the second cause of death in people between 15 and 29 years, and depression is the main cause of disability. The internal factorial structure, reliability and construct validity of the Hopelessness Scale were analyzed in upper secondary and higher education students in contexts of poverty in Mexico. 771 participants were evaluated. Reliability was examined with the coefficient omega, and validity with confirmatory factor analysis with the weighted least square mean and variance adjusted method. The value of omega was .89. The confirmatory factor analysis revealed an SRMR = .07, CFI = .95, TLI = .94, RMSEA = .05. The scale is valid and reliable for students in contexts of poverty in Mexico. Keywords: Reliability; validity; students; Beck Hopelessness Scale. Resumen: La desesperanza predice la depresión y el suicidio. En el mundo, el suicidio es la segunda causa de muerte en personas de 15 a 29 años, y la depresión es la principal causa de incapacidad. Se analizo la estructura factorial interna, fiabilidad y validez de constructo de la Escala de Desesperanza de Beck en estudiantes de educación media superior y superior en contextos de pobreza en México. 771 participantes fueron evaluados. Se examinó la fiabilidad con el coeficiente omega, y la validez con el análisis factorial confirmatorio con el método weighted least square mean and variance adjusted. El valor de omega fue de .89. El análisis factorial confirmatorio arrojó un SRMR = .07, CFI = .95, TLI = .94, RMSEA = .05. La escala es válida y fiable para los estudiantes en contextos de pobreza en México. Palabras clave: Fiabilidad; validez; estudiantes; Escala de Desesperanza de Beck.